IFAD-funded support for cassava farmers in Cambodia - International Center for Tropical Agriculture (2015)
Supported by the European Commission through the International Fund for Agricultural Development, smallholder farmers in Cambodia have been trained in improved cassava management. This supports farmers in improved environmental management while boosting yields and income, to reduce rural poverty and adapt to a changing climate.